Papel dos receptores Toll-Like 2 e 4 do estado nutricional em pacientes com leishmaniose visceral - Gatto, Mariana [UNESP] (2014)
Visceral leishmaniasis (VL) is an emerging public health problem, being of the major neglected diseases in Brazil and worldwide. It is caused by L. chagasi and L. donovani/infantum. Resistance to infection is associated to production of Th1 cytokines and susceptibility to Th2 cytokine profile. The toll-like receptors (TLRs) of the innate immunity plays an important role in microbial recognition and development of the adaptive immune response. In addition, nutritional status has a great impact on the immune response. Our objective was to evaluate the biochemical and nutritional profile, the involvement of TLR2 and TLR4 in the production of cytokines and NO and relate the lipoproteins to the immune response in VL patients, before and after the treatment. Were studied 13 patients with LV before and after the treatment and 16 control subjects. Biochemical and nutritional evaluation was performed by bioelectrical impedance and biochemical assays of total cholesterol (TC), HDL, LDL, triglycerides (TG), glucose, and total protein and fractions. Expression of TLR2 and TLR4 in lymphocytes and monocytes was performed by flowcytometry. The production of cytokines and NO in culture supernatants of PBMCs stimulated or not with agonists of TLR2 (PGN) and TLR4 (LPS) receptors was evaluated by CBA Flex technique and commercial kits. Patients on pre-treatment had lower phase angle compared to controls, reduced levels of TC, HDL, LDL and albumin and increased triglycerid elevels in relation to post-treatment and controls. In addition, pre-treatment patients presented a higher percentage of lymphocytes expressing TLR2 and TLR4 and increased expression of these receptors on monocytes. Regarding the cytokines, was observed increased of the production of TNF-α, IL-10 and TGF-β, while production of IFN- γ, IL-17 and NO were lower. The results also demonstrated the involvement of TLR2 and TLR4 receptors on TNF-α, IL-10 and NO production. With treatment ...